Willingness to compete: Between‐ and within‐gender comparisons. (6th February 2019) - Jung, SeEun; Vranceanu, Radu
Abstract : This paper introduces a new instrument to elicit individual willingness to compete (WTC). Experimental data corroborate the standard result according to which the average WTC of men is higher than the average WTC of women. However, our WTC measure reveals significant within‐gender heterogeneity: 10% of women are extremely competitive, and 13% of men are extremely averse to competition. Gender differences in WTC persist after controlling for ability, self‐confidence, tolerance for risk, and the gender of the partner.